GAMBARAN PENGETAHUAN ORANG TUA TENTANG KEBIASAAN BURUK YANG MEPENGARUHI MALOKLUSI PADA ANAK USIA PRA SEKOLAH (Politeknik Kesehatan Kemenkes Bandung, 2021)
Parents knowledge in dental care has a significant influence, so parents participation is needed in guiding, providing understanding, reminding children to maintain dental and oral hygiene, and preventing bad oral habits. Bad oral habits is a pattern of behavior that is carried out by a person repeatedly, spontaneously, and abnormally in the oral so that it interferes with the function of the oral cavity. Bad habits are the most common cause of malocclusion, the factors are frequency, intensity, and duration. This research is a descriptive study that aims to find out the description of knowledge about bad habits that affect malocclusion in preschool children. Samples were 33 parents parents who have pre-school age children in a kindergarten. Data was collected by filling out a questionnaire about controlling cross infection which is presented online in the form of Google Form. The results showed that the knowledge of parents about bad habits that affect malocclusion in pre-school children on average has good criteria with a percentage of 97%.